An Update on the State of Clinical Neuroscience of Anesthesiology - Vinall, Maria (MD Conference Express, 2014)
The FAER-Helrich Research Lecture focused on how neuroscience research is rapidly changing our understanding of anesthesia and how a deeper understanding of neuroscience can change patient care. Specific topics include the neural circuit mechanisms of commonly used anesthetics, electroencephalogram (EEG) signatures, how EEGs and their spectrograms can be used to track the state of anesthesia, how to control sedation, and how the brain dynamics under anesthesia change with age.